A survey on the consumption, knowledge and attitude of pregnant women toward the efects of folic acid on pregnancy outcome in Tabriz - MASHAYEKHI, Simin Ozar; DILMAGHANIZADEH, Maryam; SATTARI, Mohammad Reza (Iranian Journal of Child Neurology, 2011)
Objective While the effects of folic acid are well established in prevention of Neural Tube Defects (NTDs), these diseases have a high prevalence in Iran. In order to encourage folic acid supplement use in pregnancy, it is important to promote the awareness of women of childbearing age regarding folic acid importance in preventing NTDs. The aim of the present study was to study the knowledge and attitude of pregnant women on the effect of folic acid on pregnancy outcome and its use during pregnancy. Materials and Methods A questionnaire was completed by 400 women from postnatal and prenatal wards/clinics using random sampling. The questionnaire included questions regarding demographic information, folic acid consumption in pregnancy and the attitude and knowledge of the participants on folic acid supplementation and the source of information on folic acid supplementation. The questions were aimed at subjects’ knowledge of folic acid effects on fetal growth and development and prevention of NTDs and not prevention of anemia. Data was analyzed by SPSS software (ver. 13.5). Results About 89.9% used folic acid supplements at some point of the pregnancy and 53.7% knew it was beneficial for the fetus. Approximately, 25% and 34.8% of those who used folic acid believed that it was most useful when taken preconception and during the first trimester, respectively. Only 15.4% knew it could prevent NTDs. The most common information sources for folic acid use were physicians. Conclusion Awareness and use of folic acid were most prevalent among Iranian women, especially among educated ones. The results showed areas in which further work could be helpful to improve awareness regarding the benefits of folic acid. Key words: Folic acid;pregnancy; knowledge; neural tube defects (NTDs